2008
DOI: 10.1021/pr700790a
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in and Characterization of Specific Sites of Phosphorylation in Mouse and Human Histone H1 Isoforms upon CDK Inhibitor Treatment Using Mass Spectrometry

Abstract: Global changes in the phosphorylation state of human H1 isoforms isolated from UL3 cells have been investigated using mass spectrometry. Relative changes in H1 phosphorylation between untreated cells and cells treated with dexamethasone or various CDK inhibitors were determined. The specific cyclin-dependent kinase consensus sites of phosphorylation on the histone H1 isoforms that show changes in phosphorylation were also investigated. Three sites of phosphorylation on histone H1.4 isoforms have been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…3). Especially the analysis with modern mass spectrometry has revealed quite a number of novel modified residues (Garcia et al, 2004;Sarg et al, 2006;Wisniewski et al, 2007Wisniewski et al, , 2008Deterding et al, 2008). Modifications found in H1 histones primarily include phosphorylation, acetylation, methylation, and ubiquitination.…”
Section: Posttranslational Modificationmentioning
confidence: 99%
“…3). Especially the analysis with modern mass spectrometry has revealed quite a number of novel modified residues (Garcia et al, 2004;Sarg et al, 2006;Wisniewski et al, 2007Wisniewski et al, , 2008Deterding et al, 2008). Modifications found in H1 histones primarily include phosphorylation, acetylation, methylation, and ubiquitination.…”
Section: Posttranslational Modificationmentioning
confidence: 99%
“…It significantly increases during mitosis and S phase, being more specifically detected through metaphase. Multiple phosphorylated sites have been identified 84,124 and the state of H1 phosphorylation is thought to be dependent on the balance of protein phosphatase I and CDC2/CDK2 kinases.…”
Section: Roles Of Histone Phosphorylation In Chromatin Compactionmentioning
confidence: 99%
“…84 Since H1 is implicated in the stabilization of the nucleosome (as a chromatosome) and in the formation of the 30nm chromatin fiber, it has long been suggested to play a role in chromatin relaxation to allow transcription (reviewed in ref. 85).…”
mentioning
confidence: 99%
“…Most of the identified phosphorylated amino acids in the different H1 histone subtypes are part of the consensus motif (S/T)PXK recognized by cyclin-dependent kinases (CDKs), 21,22 and each of the four major cell-cycle-controlling CDKs is able to phosphorylate these different sites. 23 Recently, it was shown that a portion of histone H1.5 becomes pentaphosphorylated during mitosis.…”
Section: Introductionmentioning
confidence: 99%